HRYHORII SKOVORODA’S RHETORICAL HERITAGE - Ткаченко, Л. (New Collegium, 2020)
The article is about the legacy of Gregory Skovoroda, which was explored through the lens of contemporary rhetoric. The basic rhetorical means used in his works are identified.